Empowering Disability Communities through Inclusive Transfemoral Prosthesis Co-Design with a Local SME in Indonesia - Muslim, Khoirul; Nuryamsi, Dias; Kurnianto, Rifko Rahmat; Mihradi, Sandro (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: Lower-limb loss poses significant challenges to mobility, employability, and social participation for many individuals in low- and middle-income countries. In Indonesia, the high cost of imported prosthetics has prompted community-based small enterprises to produce low-cost transfemoral devices. Contribution: This study contributes to support a local prosthetics workshop (Independent Disabled Creativity Foundation/IDCF) by integrating user feedback and basic functional assessments to guide improvements to a transfemoral prosthesis prototype. Method: Seven transfemoral amputees completed the Locomotor Ability Index (LCI), then performed standing, walking, and stair climbing tasks assessed by the Amputee Mobility Predictor with Prosthesis (AMPPRO), Rating of Perceived Discomfort (RPD) questionnaire, and Post-test Interview with improvement concepts using the SCAMPER (Substitute, Combine, Adapt, Modify, Put to Other uses, Eliminate, Rearrange) creativity method. Results: Participants achieved independent ambulation (mean LCI = 51.00 ± 5.10; AMPPRO = 42.29 ± 3.15, K3–K4 classification). Common discomfort was reported in the amputated thigh, sound-side thigh, and ankle. Design adjustments were collaboratively proposed, including socket fit improvement, knee joint reinforcement, and coupler alignment. Conclusion: This study highlights the value of structured user feedback in guiding local prosthetic refinement. It demonstrates how participatory methods can support inclusive design and technical strengthening for community-based production.